Need analysis for a new high acuity medical psychiatry unit: which patients are considered for admission? - P. J. Caarls; M. A. van Schijndel; M. Kromkamp; A. I. Wierdsma; R. J. Osse; G. van der Hoeven; W. J. G. Hoogendijk; J. J. van Busschbach (BMC, 2019)
Abstract Background The study aims were: to estimate the proportion of patients with an indication for admission to a new high acuity Medical Psychiatric Unit (MPU), to explore the reasons for MPU-admission according to different health disciplines, and to check for differences in patient characteristics. The results of this study are to be utilized in the proposed establishment of a high-acuity MPU in a University Medical Center. Such a unit currently does not exist at Erasmus MC. Methods Hospital in-patients were included if they received psychiatric consultation from the Psychiatric Consultative Service (PCS). As part of the study protocol, psychiatrists, other medical specialists, and nurses determined the need for admission to the proposed MPU. Patient groups were compared with respect to diagnoses, socio-demographic characteristics and patient routing. Results One hundred and fifty-one patients were included, 43% had an indication for MPU-admission, for the other patients PCS involvement was sufficient. There was agreement on suicide attempts as a reason for MPU-admission. For psychiatrists, the need for further diagnostic evaluation was a common reason for MPU admission, while other medical specialists more often emphasized the need for safety measures. Patients with an unplanned hospital admission had a higher chance of MPU eligibility (OR = 2.72, 95% CI 1.10-6.70). The main psychiatric diagnoses of MPU-eligible patients were organic disorders (including delirium), mood disorders, and disorders related to substance abuse. The most common diagnoses found were similar to those in previous research on MPU populations. Conclusion Different medical disciplines have different views on the advantages of MPUs, while all see the need for such facilities. The proposed MPU should be able to accommodate patients directly from the Emergency Unit, and the MPU should provide specialized diagnostic care in an extra safe environment.